PENERAPAN MODEL PEMBALAJARAN KOOPERATIF TIPE QUICK ON THE DRAW UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS III SDN 001 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Maidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This study aims to determine whether there is an increased motivation to learn mathematics of third grade students of SDN 001 Pagaran Tapah Darussalam Rokan Hulu after application of cooperative learning model of quick on the draw. The problems of the research is